Comparisons and contrasts of the impact of the crisis on euro area labour markets - Robert Anderton; Valerie Jarvis; Béla Szörfi; Mathilde Périnet; Pavlos Petroulas; Boele Bonthuis; Peter Beck Nelleman; Thomas Conefrey; Orsolya Soosaar; Daphne Nicolitsas; Mario Izquierdo; Gregory Verdugo; et al. (European Central Bank (ECB), 2015)
The global financial and economic crisis – including two euro area recessions in 2008-2009 and 2011-2013 – has had a heavy impact on euro area labour markets. A notable feature throughout the crisis has been the considerable degree of cross-country heterogeneity of labour market adjustments – with some economies emerging relatively unscathed, while others have seen steep and persisting increases in unemployment. This paper analyses the impacts of the crisis on euro area labour markets, paying particular attention to the differential impact of the two euro area recessions of the crisis and the interplay of sectoral and institutional features driving labour market outcomes. Despite ongoing structural reforms in some euro area countries, progress has been partial and uneven across the euro area. Further reductions in labour market rigidities are necessary to increase and accelerate the adjustment capacity of euro area labour markets and help reduce the current high levels of structural unemployment.
Keywords: E24; J08; J21; J23; J24; J30; J61; J63; J64; 330; employment; Labour Demand; Labour Force; migration; Skill; Underemployment; unemployment; Vacancies; wages; Youth